Voltage Profile Analysis on a Grid with Power Injection from a Wind Farm - Noah Serem (MDPI AG, 2021)
Wind power penetration into the grid is increasing throughout the world due to centralized power generation constraints such as shortage of fossil fuel, need to reduce gas emissions, long transmission losses and need for more supply of electrical power. Connection of wind power into the grid results in power quality issues such as voltage profile changes and harmonics. This necessitates coming up with correction measures in order to meet power quality standards. This paper deals with the analysis of the effects of injecting wind power to the grid on voltage profile. Branch participation factors are used to analyze the sections of the grid where effects on voltage profile are highest due to wind power penetration. Reactive power-voltage sensitivity analysis is used to determine the buses that are more sensitive to the changes brought by the wind power injection. Two cases were considered for the injection of the wind power: IEEE 14 test bus system and IEEE 39 test bus system.